PENGALIHAN TUGAS PENGATURAN DAN PENGAWASAN PERBANKAN DARI BANK INDONESIA KEPADA OTORITAS JASA KEUANGAN BERDASARKAN UNDANG-UNDANG NOMOR 21 TAHUN 2011 TENTANG OTORITAS JASA KEUANGAN - Muchda, Metia Winati; Bachtiar, Maryati; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Regulation and supervision of bank financial institutions and non-bank financial institutions in Indonesia nowadays is done by a new independent agency called the Otoritas Jasa Keuangan (OJK) based Law Number 21 of 2011. However, the task of regulation and supervision of banks is not completely separated from the Bank of Indonesia. The shifting of the task from Bank of Indonesia to OJK be a interesting study that there are two agencies that regulate and supervise the banking. Where both institutions are equally holds the status as an independent institution which is required to be free from all of intervention by other parties. The purpose of this research are: First, to know task of Bank of Indonesia after the shifting regulation dan supervision tasks to the OJK. Second, to know independence of the OJK. Types of research used in this study is the author of normative legal research. This case study further discusses about the principles of law and comparison of law. Source of data used are secondary data sources obtained from the literature, among others, include official documents, books, research results in the form of reports and so on.The conclusion from the study are first, Bank of Indonesia still remains responsible the task of regulation and supervision of banking in section macroprudential. This resulted to should be coordination between Bank Indonesia and the OJK. Second, OJK is in fact not strictly independent.Advice from the author to the problems studied, First, OJK expected to provide legal certainty and increase the potential banking by developing an effective banking system and coordination between the OJK and Bank of Indonesia can be established. Second, the presence of several factors that affect the independence of OJK, it is expected that the parties are in the OJK to act decisively if there is intervention from other parties.Keywords : Regulation - Supervision - Banking - Bank of Indonesia - Otoritas Jasa Keuangan